Co-registering satellite images and LIDAR DEMs through straight lines. (2nd April 2016) - Elaksher, Ahmed F.
Abstract : Co-registration of optical and range data is a crucial step before they could be merged. Trustworthy correspondence between both data is determined via image registration models. These models are mainly built with points; however, with the aid of automated extraction tools for linear objects, photogrammetrists have been developing transformation models with lines. In this study, we propose to co-register satellite images and light detection and ranging (LIDAR) digital elevation models (DEMs) with straight lines. We developed a line extraction algorithm that was capable of extracting straight lines in both data sets. These lines were then utilised to register the LIDAR DEM with several high-resolution satellite images. We were able to reach one-pixel accuracy through the parallel projection transformation model and the direct linear transformation (DLT) model when geometric constraints among the lines were enforced. Our findings are similar to those reported with points and highlight the leverage of linear features in registering satellite imageries and LIDAR data.